Manifestasi Klinis Diagnosa Sindrom Diferensiasi pada Hipertensi - Harditya, Kadek Buja; Anggaraeni, Komang Rosa Tri; Sari, Ni Made Candra Citra; Wahyuningsih, Ni Luh Gede Nita Sri (STIKES Ngesti Waluyo, 2023)
Hypertension is a cardiovascular disease known by the increasing level of blood pressure and the symptoms continue to the target organ. Traditional Chinese Medicine (TCM) in acupuncture diagnosis has a different perspective regarding the clinical manifestations of hypertension as shown in organ phenomena and as syndrome differentiation. The purpose of this study was to determine the clinical manifestations and the diagnosis of syndrome differentiation in patients with hypertension. The research method was a quantitative study with one shot case study approach. The research sample was taken by using purposive sampling technique as many as 40 respondents. The results showed that the majority of respondents had hypertension in grade I conditions (57.5%), with a diagnosis of excess syndrome (75%), and liver fire flaring upward (50%). Respondents showed symptoms of irritability (67.5%), tremor (25%), tingling sensation (25%), headache (75%), epigastric pain (70%), insomnia (32.5%), nausea (10 %), and blurred vision (100%). On inspection of the tongue, it was found that the majority of the tongue was red, swollen and yellow tongue coating (67.5%), while on palpation of the pulse there was a wiry pulse (100%), rapid pulse (100%), thready pulse (52.5%), powerful pulse (75%), and weak pulse (25%). This research is the basis for the development of diagnostic in acupuncture science and acupuncture health services for people with hypertension.